The organization of scientific research work in the system of continuing education - Ivanova , O. (New Collegium, 2021)
The article considers the place and role of the system of continuing education in modern society, its components and manifestations. Scientific research work is highlighted as a key component of the continuing education model. The article describes scientific research work within the framework of the “school-university” system and specific features of its organization as exemplified by the educational and scientific complex Kharkiv University of Humanities “People’s Ukrainian Academy”. The structural elements that effectuate the system of the organization of scientific research activities of all the participants in the educational process in “People’s Ukrainian Academy” are highlighted. The specific features and key achievements in the scientific work of Kharkiv University of Humanities “People’s Ukrainian Academy” — an educational and scientific complex of continuing education — are presented. The role of scientific schools and laboratories in the formation of scientific research work at the Academy, the mechanism of their formation and functioning as well as the peculiarities of scientific work at the Academy as an experimental educational institution that implements a social experiment at the regional level in accordance with the pressing challenges of our time have been pointed out. The influence of the system of the organization of scientific work in the system of continuing education on its effectiveness and involvement of all the participants in the educational process has been described.